Modelowanie przekształceń sieci osadniczej w regionach rolniczych - Domański, Ryszard (Wydział Prawa i Administracji UAM, 1982)
Rural settlement problems require more attention from researches and research institutions. In the majority of countries in the world a considerable share of the population still lives in rural areas. This creates serious economic, social, cultural and institutional problems. At present, there is very little literature that throws light upon such problems, and suggests programs for developing the rural settlement to suit modern conditions. This paper identifies the interactions that shape the settlement network in rural regions, describes the process of restucturing, of the network, and presents a model simulating this process. Four types of interaction can be distinguished: interaction of intrafarm location forces and external forces, interaction between villages, interaction between rural and urban settlements, interaction between the rural economy and the socioeconomic environment. The analysis of these interactions leads to the conclusion that the future pattern of settlements will undergo essential transformation at the lower levels of the hierarchy. The model stimulating this transformation assumes the form of differencial equations.
Modelling the Transformation of Settlement Network in Rural Regions